A study of Chinese EFL learners' problems with stress acquisition. (February 2021) - Bu, Youhong; Zhou, Zhengdong
Abstract: This paper reports on a study of Chinese EFL learners' problems with the acquisition of English stress. The data were collected from 25 participants taking part in three recording tests designed by the authors. The three tests included: (1) a word list without any stress placement indicators or phonetic symbols, (2) a word list with stress placement indicators, and (3) three sentences with intonation phrase boundary marks. The results show that assigning wrong lexical stress, making the unstressed syllable almost as prominent as the stressed syllable in words, and giving inappropriate prominence to syllables in sentences are the significant factors contributing to a Chinese-English accent. Compared with previous studies on the L2 acquisition of English stress, this research offers a more detailed description of Chinese speakers' problems which have not been fully discussed so far. In addition, the authors analyze major reasons for the students' low performance, and suggest some pedagogical implications to deal with the errors detected. These implications, together with some applicable practice, will help develop the learners' oral competence and prevent interference errors from being fossilized.